Analysis of the Implementation of Intelligence Strategies in Hospital Pharmacy Departments - tyas, Noveyla hardhaning; Djamil, Masydzulhak; Permana, Dudi; Imaningsih, Erna Sofriana (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
Strategic Intelligence is a systematic process of collecting, analyzing, and leveraging relevant information to support decision-making and strategy development. It involves a deep understanding of the business environment, competitors, market trends, and other factors influencing an organization's success. By using strategic intelligence, organizations can identify opportunities, anticipate threats, and take appropriate steps to achieve their goals effectively. Pharmacy departments in hospitals have significant potential to generate significant revenue for the hospital. However, pharmacies often face a number of challenges that hinder operational efficiency and effectiveness. These challenges include large and excess inventories, high values of expired medications, long waiting times to obtain medications, and stock shortages. To address these challenges, the implementation of strategic intelligence in pharmacy management becomes crucial. By collecting and analyzing relevant data, pharmacies can identify patterns in medication demand, inventory trends, and causes of stockouts. By leveraging insights generated from data analysis, pharmacies can develop strategies to optimize inventory, improve the efficiency of medication delivery processes to patients, and manage medication stocks more effectively. Thus, the implementation of strategic intelligence can help hospital pharmacies improve performance, reduce waste, and enhance patient satisfaction, thereby supporting the creation of more efficient, effective, and sustainable pharmacy units in the long run.